"We Have No Influence": International Discourse and the Instrumentalisation of Transitional Justice in Burundi. Issue 3 (20th September 2013) - Taylor, David
Burundi may soon reach yet another crossroads in its tumultuous history and on its path towards transitional justice. A contentious draft law for a Truth and Reconciliation Commission awaits approval by the country's National Assembly, which has raised a number of concerns about the independence of the eventual commission, the likelihood of popular participation in the process and the prospects for criminal justice. But as this practice note seeks to demonstrate, the international community in Burundi may in fact be contributing to the instrumentalisation of the process. The note highlights how the discourse of the international community may partially facilitate a certain duplicity among influential figures within the current government, particularly with respect to compliance with stipulations under the 2000 Arusha Peace Agreement. Two common rationalisations in particular are explained that have seemingly emerged among the international community with respect to transitional justice and that are at the heart of this instrumentalisation: outside imposition and a lack of influence. The note argues that since transitional justice can no longer be regarded as an apolitical process, international actors must be more cognisant of their actions and discourse with a view to ensuring credible transitional justice processes in contexts like Burundi.